2020
DOI: 10.3390/su12176901
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Structure of the Belt and Road Initiative Research: A Scientometric Analysis and Suggestions for a Future Research Agenda

Abstract: China’s Belt and Road Initiative (BRI) has attracted increasing attention worldwide since its inception in 2013. Although the research is fast increasing in terms of publications, there is a lack of knowledge about the intellectual structure, research trends, and appropriate theories underpinning. Using bibliometric data from 1583 articles from 2013 to 2019 in the Web of Science and Scopus databases, we used bibliometric techniques and scientometric analyses to identify and analyze the intellectual structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 248 publications
(307 reference statements)
0
14
0
Order By: Relevance
“…Many studies have found that international business finance statistics has an important role in promoting the operation of enterprise groups and found that it has made outstanding contributions in controlling operating costs, improving the quality of financial work, enhancing the group's centralized control and decisionmaking ability, promoting the integration of business and finance, and improving risk control ability, etc. [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that international business finance statistics has an important role in promoting the operation of enterprise groups and found that it has made outstanding contributions in controlling operating costs, improving the quality of financial work, enhancing the group's centralized control and decisionmaking ability, promoting the integration of business and finance, and improving risk control ability, etc. [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One goal of this article has been to review and critique the academic literature on the BRI which continues chugging along, but is at risk of a wreck for reasons extensively detailed above [21]. A more important purpose is to get the literature on the BRI headed in a more fruitful direction yielding greater wins.…”
Section: Resultsmentioning
confidence: 99%
“…They are not financed out of China’s foreign aid budget, but they are subsidised by the Chinese state. The BRI framework aims to promote a parallel sustainable development strategy in other developing nations through the active sharing of working experiences, the transfer of technological capabilities, and training programmes to promote capacity building in host countries (Cao & Alon, 2020). Specifically, SEZs are a significant driver for promoting BRI’s five connectivities (policy coordination, facilities connectivity, unimpeded trade, financial integration, and people‐to‐people bonds), a key platform for international capacity cooperation, an essential way for Chinese enterprises to go global in groups and to integrate into the world, as well as realise the model of mutually beneficial cooperation among countries (Warr & Menon, 2015; Huang, 2016; Akbari et al, 2018; Pang and Huo, 2019).…”
Section: China‐led Sezs As a Potential Tool To Promote Sustainable De...mentioning
confidence: 99%